2023
DOI: 10.3389/fpsyg.2023.1126276
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering placemaking needs with(in) a kindergarten community: a cross-disciplinary approach to participatory design

Abstract: IntroductionThe design of early childhood education and care facilities faces the double challenge of creating a stimulating environment for young children and a supportive workplace for staff. The existing body of research suggests that placemaking strategies serve both requirements. A promising approach to meet placemaking needs is the participation of future occupants in the building design.MethodsWe pursued a participatory design study with the community of an Austrian kindergarten aiming to inform the fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…In our participatory design approach we deployed an adapted version of cultural probes (Gaver et al, 1999) for the children and a contextual inquiry in the form of interviews, surveys, and a building tour performed with the teachers and the headmistress of the kindergarten. The consolidated findings from our probes returns and the contextual inquiry, which we wrote about in another publication (Economidou et al, 2023), revealed the children's need for controlling their environment through placemaking and for noise mitigating strategies. These findings formed the inspiration for performing a set of PD workshops which resulted in the idea of an artefact-based HBI prototype that would support children's place-making actions and combat noise in their kindergarten environment.…”
Section: Case Study Context and Approachmentioning
confidence: 73%
“…In our participatory design approach we deployed an adapted version of cultural probes (Gaver et al, 1999) for the children and a contextual inquiry in the form of interviews, surveys, and a building tour performed with the teachers and the headmistress of the kindergarten. The consolidated findings from our probes returns and the contextual inquiry, which we wrote about in another publication (Economidou et al, 2023), revealed the children's need for controlling their environment through placemaking and for noise mitigating strategies. These findings formed the inspiration for performing a set of PD workshops which resulted in the idea of an artefact-based HBI prototype that would support children's place-making actions and combat noise in their kindergarten environment.…”
Section: Case Study Context and Approachmentioning
confidence: 73%
“…The necessity of children’s participation in research processes for the development of educational environments that support early childhood development and reveal the opportunities they desire has been emphasized in several studies (Hart, 1994; Kim, 2017; Kjørholt, 2002). However, it has also been criticized that there has been little research into listening to children’s voices to improve the spatial quality of these environments (Clark, 2010; Economidou et al, 2023; Ghaziani, 2008).…”
Section: Introductionmentioning
confidence: 99%